The Manila fashion hub - Sales, Jeannell Hazel
In order to improve the fashion status of the Philippines and make Manila the fashion capital in the region, emphasis need to be placed upon exposing the talents of the local designers to the public. The Manila Fashion Hub shall act as the central location for fashion in the city. It seeks to gather the local, regional and international fashion communities in the Philippine capital. Currently, there is no similar building or center in the Philippines. The Manila Fashion Hub shall be the first of its kind to stand in and represent the country.